ملامح الفكر التربوي عند الإمام البخاري: قراءة تحليلية لكتاب "العلم" من "الجامع الصحيح" - علي إبراهيم العجين (International Institute of Islamic Thought, 2011)
يوضح البحث مفهوم الفكر التربوي عند الإمام البخاري من كتاب العلم من الجامع الصحيح، كاشفاً عن ميزات هذا الفكر من حيث اعتماده الأحاديث الصحيحة، وشموليته، وانعكاسات التجربة الذاتية للإمام البخاري فيه. تطرق البحث إلى فكر البخاري الخاص بالأهداف التربوّية، وأصناف المتعلمين ومواصفاتهم، وطرق التعليم، والأدوات والأساليب والوسائل المعينة، ويختم البحث بعرض آراء الإمام البخاري في بعض القضايا التربوية والمصطلحات والمفاهيم الخاصّة التي احتفى بها البخاريّ دون غيره من المحدّثين والفقهاء. This paper elaborates on educational thought of Imam al-Bukhari as relayed in the chapter on Knowledge of his book al Jami' al-Sahih. It reveals features of thought, namely: its comprehensiveness, relying on sound Hadiths, and the implications of al-Bukhari's personal experience with it. The paper addresses al-Bukhari's thought relating to educational goals, types of learners, teaching methods, and supporting tools and means. It concludes with al-Bukhari's views on some educational issues, terms, and educational concepts that he, in particular, has given attention to.